Trade-union movement in kazakhstan: problems and prospects - Nurbekova, Zh.; Zhanazarova, Z.; Beissenova, A. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2016)
The main function of the trade-union organizations is consolidation of interests of workers and protection of their interests before the employer. The history of development of trade unions shows how difficult it is to satisfy needs of workers in the conditions of the market relations. While during the Soviet period trade unions were the appendix (addition) of the management of the enterprises which did not have real force of influence since the state was the employer, today trade unions try to represent interests of hired workers in practice. However, lack of experience of participation in processes of regulation of social and labor relations affects activity of trade unions and increase of level of mistrust to them from society. The government of the country is interested in development of trade unions since it is one of the most mass public organizations, by means of which development of social partnership in the social and labor sphere is possible.